Implementing Microsoft Dynamics 365 for Finance and Operations Apps : Learn best practices, architecture, tools, techniques, and more, 2nd Edition /: Learn best practices, architecture, tools, techniques, and more, 2nd Edition. (2020) - Yadav, JJ; Shukla, Sandeep; Mohta, Rahul; Kasat, Yogesh
No abstract available